Consuming for the Greater Good: "Woke" Commercials in Sports Media. (December 2022) - de Oca, Jeffrey Montez; Mason, Sherry; Ahn, Sung
Amidst a crisis in the US racial state over the summer of 2020, typically "politically" averse professional sports leagues proliferated anti-racist statements. We see the sudden advertising of corporate values and politics by sports leagues as stemming from the development of socially conscious marketing (SCM) in recent years. Marketers celebrate commercials such as Nike's Dream Crazy (2019) since they amplify the political speech of activists, such as Colin Kaepernick, and advertise ways for consumers to engage in ethical consumption. Using discourse analysis of marketing literature on SCM and textual analysis of SCM commercials shown during sporting events, we show that SCM appropriates dissent against neoliberal capitalism in order to legitimate capitalism and resist systemic change during a moment of crisis. We conclude that while we can continue to expect professional sports leagues and other brands to appear "woke, " we should not expect to see change in the exploitative conditions that make them profitable.